The use of Logistics versus Administration: A comparative and integrated analysis (Research, Society and Development, 2023)
This article aims to investigate the relationship between logistics and administration, which is a topic of great relevance for contemporary business management. Both areas play fundamental roles in the efficient functioning of organizations, however, their approaches and focuses can present significant differences. In this article, we will discuss the relationship between logistics and administration, exploring the possible interactions, synergies and challenges that exist in this context. To meet the aforementioned proposal, the following research question was outlined: what has been produced about Logistics versus Administration: A Comparative and Integrated Analysis. The main results highlight the importance of efficient integration of logistics and administration for the success of organizations, emphasizing the need for a collaborative and strategic approach. The article is prepared in a structured way, presenting a review of the key concepts between logistics and administration. Thus, this is a narrative review of the literature. The articles were surveyed in the following databases: Scopus and Google Scholar and Web of Science. In total, 157 articles were found and 20 were selected for thematic content analysis, according to the inclusion and exclusion criteria. The conclusion recaps the main research findings, emphasizing the importance of integration between logistics and administration for organizational success. It is suggested that future research explore the topics covered for a more in-depth understanding.